2021
DOI: 10.3390/app11146636
|View full text |Cite
|
Sign up to set email alerts
|

Linked Data Triples Enhance Document Relevance Classification

Abstract: Standardized approaches to relevance classification in information retrieval use generative statistical models to identify the presence or absence of certain topics that might make a document relevant to the searcher. These approaches have been used to better predict relevance on the basis of what the document is “about”, rather than a simple-minded analysis of the bag of words contained within the document. In more recent times, this idea has been extended by using pre-trained deep learning models and text re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The method's evaluation used the TREC 2004 and MSMARCO document collections. In their research, Nagumothu et al [19] demonstrated that Linked Data Triples in document relevance classification can significantly enhance the accuracy of classification in information retrieval systems based on deep learning techniques. To achieve this, they suggest constructing additional semantic features from natural language processing elements, such as named entity extraction, topic modeling, and linking these elements through Linked Data Triples.…”
Section: Related Workmentioning
confidence: 99%
“…The method's evaluation used the TREC 2004 and MSMARCO document collections. In their research, Nagumothu et al [19] demonstrated that Linked Data Triples in document relevance classification can significantly enhance the accuracy of classification in information retrieval systems based on deep learning techniques. To achieve this, they suggest constructing additional semantic features from natural language processing elements, such as named entity extraction, topic modeling, and linking these elements through Linked Data Triples.…”
Section: Related Workmentioning
confidence: 99%
“…With the entire text content as a vector space, each word in the text content will be a feature. The value of the features is provided by various term weighting techniques, such as the frequency of occurrence of the words or term frequency-inverted document frequency (TF-IDF) [10]. This method ignores the ordering of the words in the input text and is named the Bag of Words (BoW) approach [11].…”
Section: Introductionmentioning
confidence: 99%